Fully Coupled Analysis of an Integrated Floating Wind-Wave Power Generation Platform in Operational Sea-States - Chen, Mingsheng; Xiao, Panpan; Zhou, Hao; Li, Chun Bao; Zhang, Xianxiong (Frontiers in Energy Research, 2022)
The offshore wind power exploitation has experienced rapid development in recent years and has gradually moved into deeper waters with the floating wind turbine technology getting mature. Due to the strong concurrence of the wind and wave power in offshore sites, the idea of combined utilization of wind and wave power by one integrated device has attracted tremendous interests worldwide and a number of concepts and designs have been proposed. This article describes a novel integrated floating wind-wave generation platform (FWWP) consisting of a DeepCwind semi-submersible floating offshore wind turbine (FOWT) and a point absorber wave energy convertor (PAWEC). Three models including the single PAWEC, single FOWT, and FWWP are considered to investigate the feasibility of the FWWP and its advantages over the single device. Hydrodynamic analyses are first conducted using the potential flow code AQWA with the viscous correction to investigate the hydrodynamic interactions effect of the integrated model. Then, a fully coupled model for the FWWP is established by calling OpenFAST in AQWA using the F2A method. The accuracy of the established coupled model is firstly validated with OpenFAST for analysing the dynamics of the single FOWT. Finally, fully coupled analyses of the FWWP are carried out for both regular and irregular waves in the operational sea-states. The coupled dynamics and wind and wave power generation of the FWWP are compared with those of the single PAWEC and FOWT for both the regular and irregular waves.